Assessment of forage production, feed resource utilization and substitution effect of oat-vetch forage for concentrate mix on performance of sheep fed desho grass as a basal diet in Damote Gale District of Wolaita Zone, SNNPR - Mengistu, S. (Hawassa University, 2018)
This study was comprised of field survey and animal performance evaluation. Questioner based survey was conducted in project intervention and non-intervention sites where a total of 160 households participated with objective of assessing the status of improved forage production, feed resource utilization and forage seed and feed marketing in Damot Gale district. Growth and digestion experiments were conducted on 32 yearling ram lambs with mean body weight of 21.08±2.29 kg using RCBD to evaluating the substitution effect of oat-vetch forage for concentrate mix on performance of sheep fed desho grass as a basal diet. The supplementary feed treatments used over the basal diet in the study were T1 (300 g concentrate), T2 (200 g concentrate + 100 g Oat-vetch hay), T3 (100 g concentrate + 200 g oat-vetch hay) and T4 (300 g oat-vetch hay). Feed intake and body weight gain were collected during the 75 feeding days and fecal output data during 7 days of digestion trial. Mean family size (6.56), land holding (0.64) and livestock holding (3.73TLU) were discovered by the field survey. The major feed resource were desho grass (index=0.22), Crop residue (index=0.21) and grazing (index=0.21). Desho grass split was the only marketable forage planting material. Feed shortage was the primary problem (index=0.33) for livestock production. Desho and elephant grass were the dominant forage species adopted in the area. The DM intake under T1 and T2 were similar (P>0.05) but higher (P<0.05) than T3 and T4, and that of T3 was higher (p<0.05) than T4. OM, CP and ME intake were highest (P<0.05) in sheep fed T1 followed by T2 which was higher (P<0.05) than T3 and T4. T4 had lower (P<0.05) OM, CP and ME intake. T2 had highest (P<0.05) DM, OM, and NDF digestibility.. T3 had higher (P<0.05) DM, OM, CP, NDF and ADF digestibility than T1 and T4. T2 had highest (P<0.05) ADG and FCE. For 1.0 Birr investment in sheep production, Birr 3.54 and 1.45 could be obtained in T3 and T2 respectively. Hence, sheep feeding on desho grass supplemented with 100g concentrate mix and 200g oat-vetch mixed forage is a profitable business at on-farm.